Double Flip Move for Ising Models with Mixed Boundary Conditions (Journal of Computational Mathematics, 2023)
This note introduces the double flip move to accelerate the Swendsen-Wang algorithmfor Ising models with mixed boundary conditions below the critical temperature. Thedouble flip move consists of a geometric flip of the spin lattice followed by a spin valueflip. Both symmetric and approximately symmetric models are considered. We prove thedetailed balance of the double flip move and demonstrate its empirical efficiency in mixing.